An Exploratory Study of "Quantitative Linguistic Feedback": Effect of LENA Feedback on Adult Language Production. (August 2013) - Suskind, Dana; Leffel, Kristin R.; Hernandez, Marc W.; Sapolich, Shannon G.; Suskind, Elizabeth; Kirkham, Erin; Meehan, Patrick
A child's early language environment is critical to his or her life-course trajectory. Quantitative linguistic feedback utilizes the Language ENvironment Analysis (LENA) technology as a tool to analyze verbal interactions and reinforce behavior change. This exploratory pilot study evaluates the feasibility and efficacy of a novel behavior-change strategy, quantitative linguistic feedback, to influence adult linguistic behavior and, as a result, a child's early language environment. Baseline LENA outcome measures (i.e., adult word count [AWC] and conversational turn count [CTC]) were obtained from a diverse sample of 17 nonparental caregivers and their typically developing children (charges) ages 10 to 40 months. Caregivers participated in a one-time educational intervention focusing on enriching a child's home language environment, interpreting feedback from the baseline LENA recordings, and setting language goals for the following session. Post-intervention, six additional LENA recordings were obtained weekly to measure linguistic behavior. Caregivers showed a significant and prolonged increase from mean baseline to mean postintervention AWC and CTC as measured by LENA–AWC: mean difference = 395 words per hour, 31.6% increase, t = 3.29, p < .01; CTC: mean difference = 14 turns per hour, 24.9% increase, t = 3.54, p < .01. Preliminary results indicate that a one-time educational intervention combined with quantitative linguistic feedback may have a positive effect on caregiver language output, thus enhancing the child's language environment. This study represents an initial step in the development and evaluation of a novel behavior-change strategy. We propose that quantitative linguistic feedback will add significantly to the arsenal of clinical and research tools used to evaluate and enrich a child's early language environment.